Exploring the Mechanisms of Allergic Contact Dermatitis: Lipid Peroxidation, CD1 Antigen Presentation and Effects on Skin Lipids - Clancy, Aoife (Trinity College Dublin. School of Pharmacy & Pharma. Sciences. Discipline of Pharmacy, 2026)
Allergic contact dermatitis (ACD) affects around 20% of the population and significantly impairs quality of life. While protein-based mechanisms of ACD are well characterised, the contribution of lipids remains poorly understood. Lipids are abundant and highly re-active skin components, implicated in multiple inflammatory dermatoses, yet their role in ACD has been underexplored. This thesis investigates the involvement of lipids in ACD, focusing on the ability of metal allergens to induce lipid peroxidation, the potential con-tribution of lipid peroxidation to cell death, the role of lipid antigen presentation mole-cules CD1a and CD1d, and the penetration and lipidome-modifying effects of small organ-ic allergens in skin. Chapter 2 examined the ability of nickel (II) sulfate (NiSO), cobalt (II) chloride (CoCl), and potassium dichromate (KCrO) to induce lipid peroxidation in both a linoleic acid single-lipid system and HaCaT keratinocytes, using the C11-BODIPY 581/591 assay. All three metals induced peroxidation in the lipid model. In HaCaTs, chromium triggered strong peroxidation across all concentrations, while nickel and cobalt did so only at higher lev-els, coinciding with reduced cell viability. These findings raised the key question of whether lipid peroxidation is a cause or a consequence of toxicity. Chapter 3 investigated the mechanism of metal-induced cell death. Annexin-V/PI staining and cell cycle analysis indicated necrotic, rather than apoptotic, pathways. Ferroptosis inhibitors ferrostatin-1 (Fer-1) and deferoxamine (DFO) were tested to assess the role of ferroptosis, a lipid peroxidation-driven form of death. Neither inhibitor rescued cells from metal-induced toxicity. However, limitations in Fer-1 performance reduced the strength of these conclusions, and further work is needed to further characterise metal induced cell death. Chapter 4 explored whether CD1a and CD1d antigen-presenting molecules contribute to ACD through recognition of metal-induced lipid changes. NiSO enhanced T cell activa-tion and TH1 cytokine production in nickel-allergic donors in both a CD1a- and CD1d-dependent manner. Cobalt and chromium produced little CD1-dependent activity. Nota-bly, lipid peroxidation products showed molecule-specific effects: 4-hydroxynonenal (4-HNE) activated cytokine responses through CD1a, whereas malondialdehyde (MDA) did so via CD1d. These findings identify novel pathways by which lipids and CD1 molecules may contribute to nickel ACD. Chapter 5 examined the penetration of low molecular weight organic allergensmethylisothiazolinone (MI), linalool hydroperoxide (LinOOH), and limonene hydroperox-ide (LimOOH)into ex vivo human skin using Time-of-Flight Secondary Ion Mass Spec-trometry. MI penetrated into the viable epidermis, while LinOOH and LimOOH remained mainly in the stratum corneum with limited deeper penetration. All allergens significantly altered skin lipid composition, reducing or modifying key lipids such as cholesterol, mon-oacylglycerols, diacylglycerols, and phosphatidylcholine, indicating a broader impact of allergens on skin barrier lipid integrity. Overall, this work highlights metals as inducers of lipid peroxidation, identifies roles for CD1a/CD1d in nickel ACD, and shows organic allergen penetration and lipidome disrup-tion in skin. These findings provide new insights into lipid contributions to ACD and sug-gest lipid pathways and antigen presentation molecules as potential therapeutic targets.
APPROVED
Keywords: Allergic Contact Dermatitis; Metal Allergy; Lipid Peroxidation; Skin Lipids